YOUTUBE ADVERTISEMENT SEBAGAI IMPLEMENTASI KOMUNIKASI BISNIS PADA PRODUK SKINCARE LOKAL - Sabila Nurul Fauziah; Cecep Safa’atul Barkah; Lina Aulina; Iwan Sukoco (Scriptura, 2022)
Skincare is an industry that’s being warmly discussed for its development. The emergence of many local skincare brands has begun to color competition in beauty industry. In expanding market and introducing its products to potential customers, company carries out promotional activities, that’s advertising on YouTube. Purpose of this study was to find out the application of Youtube advertisements to local skincare products by reviewing the delivery of messages by MS Glow, Scarlett and Somethinc. Research method used is qualitative approach with descriptive research. In addition, content analysis was also carried out by reviewing message delivery, visuals displayed, and reactions/reviews from consumers who were carried out through Youtube Ads. Local skincare brands such as MS Glow, Scarlett, and Somethinc have their own characteristics in conveying their messages and visual concepts that are displayed through their Youtube Ads. Ms. Glow by conveying soft sell that leads to consumer feelings and visual concept of comedy, Scarlett uses soft sell and fresh and colorfull visuals, while Somethinc uses hard sell by directing the invitation to buy her product and white visuals depicting the coolness. Youtube Ads as implementation of business communication will convey all information that company wants to convey to its consumers.